HUBUNGAN PENGETAHUAN IBU DENGAN PENGEMBANGAN MENTAL DAN MOTORIK ANAK USIA 6-12 BULAN DI KABUPATEN TANAH DATAR PROVINSI SUMATRA BARAT - Rina Hasniyati; M Husni Thamrin; Marni Handayani (Politeknik Kesehatan Tanjung Karang, 2013)
Rina Hasniyati1)M.Husni Thamrin1) Marni Handayani1)1)Poltekkes Kemenkes Padang ABSTRACT: Associated Knowledge Of Mother With Motorik And Mental Development Stunted Children Ages 6-12 Months In Tanah DatarRegency The District Of West Sumatra Province. Infancy (0-12 months) is the most important period in human development. This is due in this period of brain development and intelligence that will affect adulthood (Winarno, 1990). Developmental disorder is a condition in which the child is not able to achieve the developmental tasks at the expected time. Disorder can occur in many areas of development, for example in motorik, language, social, or think. Based on the UNICEF conceptual framework, there are direct and indirect factors that affect child development (Myers 1990; and 1997 in Hartoyo Hadad et al. 2000).This study aims to determine the relationship of nutrition knowledge of mothers with levels of motorik and mental development of stunted children aged 6 to 12 months in Tanah Datar regency. This study uses a quantitative approach with cross sectional design and qualitative approaches. The samples were stunted children aged 6-12 months as many as 89 people. Sampling was carried out with Multistage Random Sampling technique. Data analysis was performed with a statistical test and Chi square test. The results quantitatively demonstrate an association with maternal nutrition knowledge of motorik and mental development of stunted children with p value 0.02. It is recommended to improve the coordination between the programs in health centers (posyandu), so that health problems, especially problems of child development can be satisfactorily resolved. Besides cross-sector participation as kenagarian, PKK and related agencies in the revitalization posyandu further enhanced, so that posyandu as one of community empowerment efforts can work well. Key words :motorik and mental development of stunted children Abstrak. Hubungan Pengetahuan Ibu dengan Pengembangan Mental dan Motorik Anak Usia 6-12 Bulan Kabupaten Tanah Datar Provinsi Sumatra Barat.Anak usia(0-12 bulan) adalah periode yang palingpenting dalampembangunan manusia. Hal ini disebabkandalam periodeperkembangan otakdan kecerdasanyang akan mempengaruhimasa dewasa(Winarno, 1990). Gangguan perkembanganadalah suatu kondisidi manaanak tidakmampu mencapaitugas perkembanganpadawaktu yang diharapkan. Gangguandapat terjadi dalam berbagaibidang pembangunan, misalnya dalammotorik, bahasa, sosial, atau berpikir. Berdasarkankerangka konseptualUNICEF, ada faktor-faktorlangsung dan tidak langsungyang mempengaruhiperkembangan anak(Myers 1990,. Dan 1997diHartoyoHadadetal, 2000).Penelitian inibertujuanuntuk mengetahui hubunganpengetahuangiziibu dengantingkatperkembangan motorik danmental anakstuntedusia 6 sampai 12bulandi KabupatenTanah Datar. Penelitian ini menggunakanpendekatan kuantitatifdengandesaincross sectionaldan pendekatankualitatif. Sampelterhambatanak usia6-12 bulansebanyak89orang. Pengambilan sampel dilakukandengan tekniksamplingMultistagerandom. Analisis data dilakukandenganuji statistikdanuji Chi square.Hasilkuantitatifmenunjukkan hubunganpengetahuangizi ibumotordanperkembangan mental anakterhambatdengannilaip=0,02.Disarankanuntuk meningkatkankoordinasi antaraprogramdi puskesmas(posyandu), sehingga masalahkesehatan, terutama masalahperkembangan anakdapat diselesaikan. Selainpartisipasilintas sektorsepertikenagarian, PKKdan instansi terkaitdalam revitalisasiposyandulebih ditingkatkan, sehinggaposyandusebagai salah satuupaya pemberdayaan masyarakatdapatbekerja dengan baik Kata kunci:perkembangan motorik danmental anak